Identifikasi Pemanfaatan Obat Herbal Pada Ibu Nifas - Citra Hadi Kurniati; Atika Nur Azizah (JIDAN (Jurnal Ilmiah Bidan), 2021)
Background: Herbal medicine is a drug derived from a mixture of natural ingredients in the form of herbs in the desired formulation. The use of herbal medicine has now grown rapidly with the use of ingredients from nature. The use of this herbal remedy is used not only for sick people, but for health recovery for example in postpartum mothers. Beliefs are hereditary so that there are still many who use traditional ingredients in their treatment and in the treatment of postpartum. Purpose: Knowing the utilization of herbal medicine in mothers nifas in the working area of Puskesmas Cilongok 2 Banyumas Regency. Method: Qualitative research with case study design. The subjects of the study were Nifas'mother, her husband and the village midwife. Data analysis in this qualitative research uses thematic content analysis. Results: Types of herbal plants used in mother nifas are turmeric, tamarind, and katuk. Conclusion: Herbal medicine is utilized by the public because the belief factor is traditionally and hereditary obtained by growing their own herbal plants. Types of herbal plants that are used are turmeric, tamarind, and katuk